Transformation of GRAFCET Into GAL for Verification Purposes Based on a Detailed Meta-Model - Robin Mross; Aron Schnakenbeck; Marcus Volker; Alexander Fay; Stefan Kowalewski (IEEE Access, 2022)
The graphical modeling language GRAFCET is used as a formal specification language in industrial control design. To use these formal specifications for model-driven development of control code it is beneficial to ensure their syntactical and semantic correctness. Therefore in this paper, a detailed meta-model for GRAFCET is presented, which takes so-called terms into account, i.e. logical and arithmetic expressions in conditions and assignments. The meta-model and additionally proposed invariants allow the creation of syntactically correct GRAFCET instances. Based on this, a translation of GRAFCET to Guarded Action Language (GAL) is presented. The resulting transition system in GAL forms the basis for a semantic analysis of the GRAFCET instances by means of model checking in future research. Finally, the models are then employed for automatic code generation in Structured Text.